Analisis Pengaruh Aglomerasi Industri, Angkatan Kerja, Dan Human Capital Investment Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2017-2019 - Melantika Destya Windasari; Suhesti Ningsih; Yuwita Ariessa Pravasanti (Jurnal Akuntansi dan Pajak, 2021)
This study aims to examine the effect of industrial agglomeration, labor force, and human capital investment on the economic growth of regencies/cities in Central Java Province. This type of research includes quantitative research using secondary data from 35 regencies/cities in Central Java Province in 2017-2019 obtained from the Central Statistics Agency. The model used is multiple regression analysis with a fixed effect model. The result of the study show that industrial agglomeration, labor force, and human capital investment simultaneously have a significant effect on economic growth. Partially, this study shows that industrial agglomeration does not have a significant effect on economic growth. Meanwhile, the labor force and human capital investment have a significant effect on economic growth.